Habitat use by threatened sheldgeese (Chloephaga spp.) in Austral Patagonia at two spatial scales - Cossa, Natalia Andrea (2021)
Upland Goose Chloephaga picta, Ashy-headed Goose Chloephaga poliocephala and Ruddy-headed Goose Chloephaga rubidiceps are endemic goose-like threatened birds of southern South America. This work aimed to study how sheldgeese are distributed both temporally and spatially and characterize their habitat use in part of their breeding range in Southern Argentina, a little-explored subpolar region. We conducted nine surveys between spring 2013 and summer 2016 across a maximum of 235 km in Santa Cruz and 698 km in Tierra del Fuego per survey. We recorded the presence of non-breeding sheldgoose groups and Upland Goose pairs. We collected data at site-scale (~ 0.8 km2) and extracted data from geographic information systems for landscape-scale (5 km2) analyses. We recorded 2396 non-breeding groups containing one, two or the three species, 788 Upland Goose pairs and 102 solitary individuals. The Upland Goose was present in almost all groups and was the most abundant sheldgoose, followed by the Ashy-headed Goose. The Ruddy-headed Goose was observed only in 15 locations. Poa grasslands, meadows and Festuca grasslands were the habitats in which we detected most individuals. Sheldgoose density was higher in Tierra del Fuego than in Santa Cruz, and increased from spring to autumn and decreased in winter. The largest sheldgoose groups were concentrated in meadows and waterbodies. Sheldgeese selected sites with greater habitat diversity, habitat richness and number of habitats patches. Our results provide information to understand which environmental conditions favour sheldgeese and to aid in the selection of important areas for the conservation of these species.